CRAFTING LASTING IMPRESSIONS OF HINDU TOURISM IN BALI : THE ROLE OF MEMORABLE TOURISM EXPERIENCES IN BUILDING STRONG DESTINATION BRANDS AND ATTACHMENT - Khoirun Nisa; Soomro, Suhaib Ahmed (Fakultas Dharma Duta UHN IGB Sugriwa Denpasar, 2025)
This study explores the impact of memorable tourism experiences (MTEs) on destination brand equity and destination attachment of Hindu tourism in Bali. It aims to elucidate how these experiences shape tourists' perceptions and behaviors. MTEs are characterized by their uniqueness and ability to create lasting impressions, significantly influencing tourist satisfaction and loyalty. The research employs partial least squares structural equation modeling (PLS-SEM) to examine the relationships between MTEs, destination brand equity, and destination attachment. Findings reveal that memorable tourism experiences significantly enhance destination brand equity by fostering strong emotional connections and increasing perceived value. Additionally, MTEs positively influence destination attachment, which in turn strengthens brand loyalty. The study highlights the critical role of authenticity and immersive experiences in building and sustaining a destination's appeal. These insights offer valuable implications for tourism management and marketing strategies, emphasizing the importance of creating impactful experiences to differentiate destinations and foster long-term visitor engagement.